Defects in the Pronunciation of Sounds in Children with Weak Hearing and Their Elimination (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Speech communication is the most important factor in the development of a child as a person. Speech development is directly related to hearing. This article provides information on the importance of speech in hearing-impaired children, the role of auditory activity in speech development, the level of speech development in a healthy and hearing-impaired child, and the direction of corrective work with hearing-impaired children.